Efektivitas Media Sosial Tiktok dalam Membangun Brand Image Perusahaan Mie Gacoan - Hana Zulfia; Arfian Suryasuciramdhan; Siti Dhifah Umairah; Cindy Nurlaila; Sharla Setyawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This research discusses the role of TikTok social media in building the brand image of Mie Gacoan restaurant. PT Pesta Pora Abadi has a subsidiary company engaged in the food sector, namely Mie Gacoan, which focuses on selling spicy noodles. Mie Gacoan is the No. 1 Spicy Noodle brand in Indonesia, Mi Gacoan relies on social media as the main tool in marketing their products. Platforms such as Instagram and TikTok are important means to reach the target market, especially among young people. Therefore, in this study, researchers use qualitative methodology with a literature study approach model, namely to find out about the role of social media in building a brand image (Mie Gacoan case study). The system used is carried out through searching, reading, listening, taking notes from significant previous research, which is sourced from national books and journals. The focus of this research is how the role of TikTok, the strategy used, and the impact of its use of social media on the image of the Mie Gacoan brand. The purpose of this study is to analyze the role of TikTok, identify the strategies used, and evaluate the impact on the brand image and company performance.